UJI KANDUNGAN LOGAM BERAT AIR LINDI DI TPA MUARA FAJAR RUMBAI PEKANBARU - Ade Pulasta Siprana; Riski Novera Yenita (EcoNews, 2020)
The presence of a final processing site (TPA) often creates a dilemma often causing air pollution. Pollution can occur in the air as a result of waste decomposition, it can also contaminate water and soil caused by leachate leakage that will impact on health problems, but it is necessary because it is also a material search for life for the society. Waste landfill caused by garbage dumps with a very large volume of volume so that it is deposited with rain water and produce a leachate water (water that deposited waste) causes the quality of water to be bad resulting in decreasing quality of water quality around. The purpose of this research is to know the heavy metal content of leachate water at TPA Muara Fajar Rumbai Pekanbaru. The study was conducted in June 2016 - December Place of sampling that is at TPA Muara Fajar Pekanbaru. Place to conduct a leachate water leachate analysis at UPT Testing Laboratory Office of Public Works of Riau Province. The method used in this research is survey, where the Muara Fajar Pekanbaru TPA is used as the sampling location. Samples taken then analyzed the heavy metal content (Pb, Cd, Cu) in the laboratory, then the data obtained were analyzed descriptively in accordance with SNI 06-2412-1991. The content of heavy metals cadmium (Cd) in leachate water in ponds 1 and 2 of 0.8 mg / ppm, while in pond 3 of 0.7 mg / ppm exceeded the predefined quality standard. The content of heavy metals copper (Cu) in leachate water in pond 1 of 3.1 mg / ppm, in pond 2 of 3 mg / ppm exceeded the predetermined quality standard and in pond 3 of 2.9 mg / ppm below the standard quality that has been set. The content of lead weight metal (Pb) in ponds 1 and 2 was 2.26 mg / ppm, while in pond 3 of 2.24 mg / ppm exceeded the predefined quality standard.